Similarities and differences of a proliferation-inducing ligand expression in lacrimal gland lesions of patients with IgG4-associated ophthalmic diseases and mucosa-associated lymphoid tissue lymphoma - He, Lvfu; Zhan, Lisha; Yang, Yu; He, Weimin (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the expression condition of a proliferation-inducing ligand (APRIL) in lacrimal gland lesions of patients with IgG4-associated ophthalmic diseases (IgG4-ROD) and mucosa-associated lymphoid tissue (MALT) lymphoma.Patients and methodsFifteen patients with IgG4-ROD, 3 with MALT lymphoma, and 1 with elevated IgG4 with lacrimal gland lesions, treated in West China Hospital of Sichuan University from April 2022 to November 2023, were included. Immunofluorescence staining was used to detect the expression of APRIL in the specimen of lacrimal gland.ResultsThe average expression level of APRIL in patients with lacrimal gland lesions of IgG4-ROD and MALT lymphoma were 8471.12 pixels/HPF and 2950.78 pixels/HPF respectively. The positive rates of APRIL were 10.49% and 7.23% respectively. CD138 and APRIL were colocalized, and the positive rate of their colocalization was 8.83%, and the positive areas of colocalization coincidence was 946.84 pixels/HPF in patients with IgG4-ROD. CD20 and APRIL were colocalized, and the positive rate of their colocalization was 7.04%, and the positive areas of colocalization coincidence was 949.78 pixels/HPF in patients with MALT lymphoma. We also found that the expression level and the positive rate of APRIL were positively correlated with the level of serum IgG4 in IgG4-ROD patients (r=0.5820, P=0.029; r= 0.6261, P=0.017; respectively). In addition, the positive rate and the positive areas of CD138 and APRIL colocalization were also positively correlated with serum IgG4 level (r=0.6420, P=0.013; r= 0.5673, P=0.034; respectively).ConclusionAPRIL is highly expressed in lacrimal gland lesions of patients with IgG4-ROD and MALT lymphoma. This overexpression may facilitate the enrichment of CD138+ plasma cells and is associated with elevated serum IgG4 levels in patients with IgG4-ROD. Additionally, it may promote the proliferation of CD20+ B lymphocytes in patients with MALT lymphoma.APRIL may play a certain role in the possible transformation of IgG4-ROD into MALT lymphoma.